Colloidal Synthesis and Photophysics of M3Sb2I9 (M=Cs and Rb) Nanocrystals: Lead‐Free Perovskites. Issue 45 (9th October 2017) - Pal, Jaya; Manna, Suman; Mondal, Anirban; Das, Shyamashis; Adarsh, K. V.; Nag, Angshuman
Abstract: Herein we report the colloidal synthesis of Cs3 Sb2 I9 and Rb3 Sb2 I9 perovskite nanocrystals, and explore their potential for optoelectronic applications. Different morphologies, such as nanoplatelets and nanorods of Cs3 Sb2 I9, and spherical Rb3 Sb2 I9 nanocrystals were prepared. All these samples show band‐edge emissions in the yellow–red region. Exciton many‐body interactions studied by femtosecond transient absorption spectroscopy of Cs3 Sb2 I9 nanorods reveals characteristic second‐derivative‐type spectral features, suggesting red‐shifted excitons by as much as 79 meV. A high absorption cross‐section of ca. 10 −15  cm 2 was estimated. The results suggest that colloidal Cs3 Sb2 I9 and Rb3 Sb2 I9 nanocrystals are potential candidates for optical and optoelectronic applications in the visible region, though a better control of defect chemistry is required for efficient applications. Abstract : Lead astray : Colloidal nanocrystals of Cs3 Sb2 I9 and Rb3 Sb2 I9 perovskites with different shapes (sphere, rod, platelet) were prepared and show excitonic absorption (high cross‐section ca. 10 −15  cm 2 ) and emission in the red–yellow region. Exciton many‐body interactions were studied using femtosecond transient absorption spectroscopy. The Sb‐halide nanocrystals show potential as Pb‐free optoelectronic material.